Pentingnya Mengetahui Golongan Darah Sejak Dini sebagai Identitas Diri - Rumeyda Chitra Puspita; Lucia Sincu Gunawan; Reny Pratiwi (Health Care : Journal of Community Service, 2026)
Blood group identification from an early age is an important aspect of health awareness and serves as a personal identity that can support emergency management, such as anemia and blood transfusion needs. This community service activity aimed to improve students’ knowledge and awareness regarding the importance of knowing their blood group through health education and direct examination. The methods included health education on the importance of blood groups and anemia prevention, followed by ABO and Rhesus blood group examination using the agglutination method with Anti-A, Anti-B, Anti-AB, and Anti-D antisera from capillary blood samples. The subjects consisted of elementary and junior high school students, including 60 students from SMP 12 Surakarta, 50 students from SMP 18 Surakarta, and 50 students from MIAI Grobogan. The results showed that most respondents in SMP 12 (70.0%) and SMP 18 (88.0%) were aged 13–15 years, while MIAI Grobogan was dominated by students aged 11–12 years (56.0%). The level of knowledge was still low in SMP 12 (23.3%) and SMP 18 (36.0%), but higher in MIAI Grobogan (64.0%). Most students showed a neutral response toward the examination, although fear was higher in MIAI Grobogan (60.0%). Overall, blood group distribution was dominated by type O (30.6%) and A (27.5%), followed by B (25.6%) and AB (16.3%). In conclusion, this activity was effective in improving students’ knowledge and awareness regarding the importance of blood group identification; however, continuous educational reinforcement is still needed.